Aspirasi Pendidikan Tinggi Pemuda di Kabupaten Klaten sebagai Kerja Generasi dalam Konstruksi Identitas - Warda, Yusnita Silsilia (Universitas Gadjah Mada, 2023)
This article qualitatively explores the production processes of higher education aspirations among students and recent graduates of upper secondary schools in Klaten Regency. Considering the socio-spatial and temporal context, this study examines the dynamics of aspirations in the ‘desakota’ region in the digital age, an area that has been relatively under-researched. Data generation in this study primarily relies on in-depth interviews with eleven participants. Employing the concepts of identity and generations, this study reveals that higher education aspirations are refinements of individual narratives constructed through interactions with adults and peers in educational, familial, and digital settings. Situated in an in-between area, the production process of aspirations among Klaten’s youth reflects an ambiguity as traditional factors collide with values brought by modernity. I propose that aspirations for higher education in this context are both social and individual projects, encompassing not only the future, but also the present matters through which youth fashion themselves. This mirrors the critics towards developmental approach that frames educational aspirations predominantly as rational and personal decisions aimed at achieving upward social mobility.